Bioethanol production from alkali-pretreated rice straw: effects on fermentation yield, structural characterization, and ethanol analysis - Ningthoujam, Reema; Jangid, Pankaj; Yadav, Virendra Kumar; Sahoo, Dipak Kumar; Patel, Ashish; Dhingra, Harish Kumar (Frontiers in Bioengineering and Biotechnology, 2023)
In the current ethanol production technology, the conversion of lignocellulosic biomass to efficient fermentable sugars is in dire need. The conversion requires pretreatment of the biomass, which is one of the most expensive steps, and thus it is quite necessary to search and select the best effective method, which is both cost-effective and high efficiency. In this study, rice straw (RS) biomass was pretreated using 4% NaOH alkali, soaked for 4 h, and further autoclaved for 30 min. The structural and morphological changes were examined using Fourier Transform Infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM) analysis in both native and alkali-treated RS. The FTIR analysis revealed that native RS contains a considerable amount of lignin, which was removed after the pretreatment process. The XRD pattern of the RS revealed increasing crystallite size of the pretreated lignocellulosic biomass. The study of SEM clearly showed the distorted structure and surface porosity after the pretreatment process. Enzymatic hydrolysis efficiency was checked by comparing the commercial enzymes and microbial hydrolysis extracted from a fungal isolate. The best-reducing sugar yield obtained was 0.62 g/L, achieved at optimized conditions from the commercial enzymes. Also, fermentation efficiency was checked using the yeast isolate Saccharomyces cerevisiae in both the native and pretreated substrate, and it was found that the highest ethanol concentration (21.45%) was achieved using 20% w/v biomass loading, enzyme loading (2:1:1), 30°C and pH 4.5 for a week fermentation which was higher than that of the untreated RS (3.67%). The ethanol thus produced was further checked for analysis by the 1 H nuclear magnetic resonance (NMR) and 13 C method.